Peyer's patches: organizing B‐cell responses at the intestinal frontier. Issue 1 (May 2016) - Reboldi, Andrea; Cyster, Jason G.
Summary: Secondary lymphoid tissues share the important function of bringing together antigens and rare antigen‐specific lymphocytes to foster induction of adaptive immune responses. Peyer's patches (PPs) are unique compared to other secondary lymphoid tissues in their continual exposure to an enormous diversity of microbiome‐ and food‐derived antigens and in the types of pathogens they encounter. Antigens are delivered to PPs by specialized microfold (M) epithelial cells and they may be captured and presented by resident dendritic cells (DCs). In accord with their state of chronic microbial antigen exposure, PPs exhibit continual germinal center (GC) activity. These GCs not only contribute to the generation of B cells and plasma cells producing somatically mutated gut antigen‐specific IgA antibodies but have also been suggested to support non‐specific antigen diversification of the B‐cell repertoire. Here, we review current understanding of how PPs foster B‐cell encounters with antigen, how they favor isotype switching to the secretory IgA isotype, and how their GC responses may uniquely contribute to mucosal immunity.